Language, the Singer and the Song: The Sociolinguistics of Folk Performance - Watts, Richard J. and Morrissey, Franz Andres (United Kingdom: Cambridge University Press, 2019)
This book offers a thorough and convincing sociolinguistic exploration of folk songs.The book refreshes and enlarges our understanding of language and music as communication systems.The relationship between language and music has much in common-rhythm, structure, sound, metaphor. This book presents a sociolinguistic model for analysing them.
Includes Bibliographic references and index.
Keywords: Music-Performance--Social aspects----Music and Language--Folk Songs